2014
DOI: 10.1111/bph.12667
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of hypothalamic PI3KSTAT3 signalling in regulating appetite suppression mediated by amphetamine

Abstract: BACKGROUND AND PURPOSEAppetite suppression induced by amphetamine has been attributed to its inhibition of neuropeptide Y (NPY) neurons and activation of pro-opiomelanocortin (POMC) neurons in the hypothalamus. This study examined whether STAT3 was involved in these actions of amphetamine. EXPERIMENTAL APPROACHRats were given amphetamine daily for 4 days. Changes in the expression of NPY, POMC, melanocortin MC3 receptors, PI3K and STAT3 in the hypothalamus were assessed by RT-PCR and Western blotting. Antisens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 58 publications
(67 reference statements)
1
12
0
Order By: Relevance
“…In this way, experiential variables like delay pre-exposure may be used as an experimental tool similar to pre-session drug administration in behavioral pharmacology (e.g., use of anxiolytic drugs to examine the role of anxiety in experimental paradigms). We note, however, that the varied behavioral effects of pharmacological treatment (e.g., on the reinforcing efficacy of food, discrimination of reinforcer contingencies, or motor behavior; Chu et al, 2014; Johnson, Stein, Smits, & Madden, 2013; Hoffman & Benninger, 1985) often make it difficult to attribute changes in behavior to precise mechanisms. In the abstract, delay pre-exposure may recruit fewer of these nuisance variables and would therefore be better suited for use in experimentation.…”
Section: Discussionmentioning
confidence: 95%
“…In this way, experiential variables like delay pre-exposure may be used as an experimental tool similar to pre-session drug administration in behavioral pharmacology (e.g., use of anxiolytic drugs to examine the role of anxiety in experimental paradigms). We note, however, that the varied behavioral effects of pharmacological treatment (e.g., on the reinforcing efficacy of food, discrimination of reinforcer contingencies, or motor behavior; Chu et al, 2014; Johnson, Stein, Smits, & Madden, 2013; Hoffman & Benninger, 1985) often make it difficult to attribute changes in behavior to precise mechanisms. In the abstract, delay pre-exposure may recruit fewer of these nuisance variables and would therefore be better suited for use in experimentation.…”
Section: Discussionmentioning
confidence: 95%
“…This leads to an increase in metabolic rate and stimulation of anorectic hypothalamic neurocircuits and other brain areas. In the hypothalamus, monoaminergic neurons project from the arcuate nucleus to the median eminence, and amphetamine stimulation of monoamine release inhibits food intake via stimulation of proopiomelanocortin (POMC) neuronal activity, whereas neurons expressing neuropeptide Y (NPY)/agouti-related peptide (AgRP) are inhibited (Heisler et al, 2002(Heisler et al, , 2006Kuo, 2005Kuo, , 2006Garfield and Heisler, 2009;Kuo et al, 2009Kuo et al, , 2012Roepke et al, 2012;Chu et al, 2014;Jones and Bloom, 2015).…”
Section: B 24-dinitrophenolmentioning
confidence: 99%
“…However, following the co‐administration of ERK antisense/amphetamine, the partial reversal of pERK/pCREB/NPY/POMC/MC 3 receptor expression was about 30–50% compared to normal levels, implying the possibilities that (i) antisense ERK did not delete ERK completely (only 60% reduction), and (ii) ERK‐CREB signalling was not the only pathway involved in the induction of NPY/POMC gene expression in the amphetamine‐treated rats. Previous reports revealed that some transcription factors, such as AP‐1 (Hsieh et al, ), NF‐κB (Kuo et al, ) and STAT3 (Chu et al, ), and some cytoplasmic factors, such as PI3K (Chu et al, ), anti‐oxidative enzymes (Hsieh et al, ), PKC (Kuo et al, ) and PKA (Hsieh et al, ), were also activated and involved in regulating NPY/POMC gene expression during amphetamine treatment. Some previous reports revealed that ERK co‐operates with other transcription factors in the brain in the control of behaviour‐associated diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Its anorectic effect is associated with the central release of dopamine, which in turn can decrease NPY but increase POMC expression in the hypothalamus (Gillard et al, ; Chen et al, ; Hsieh et al, ). In addition, NPY and POMC may function reciprocally in the control of amphetamine‐mediated appetite suppression (Fioramonti et al, ; Hsieh et al, , ; Chu et al, ). The melanocortin receptor (MC receptor) belongs to the family of POMC system, which can regulate feeding behaviour and energy expenditure (Butler, ).…”
Section: Introductionmentioning
confidence: 99%